OPERATION OF THE CALL CENTER AT A HIGH-TECHNOLOGY PEDIATRIC MEDICAL INSTITUTION (WITH COMMENTARY BY A.A. MODESTOV) - I. N. Chernomurov; S. A. Dukoyan (Педиатрическая фармакология, 2014)
Introduction of modern information systems is one of the important objectives of medicine, as it contributes to higher availability of medical services for the population. Public relations of medical organizations involve websites of these organizations, outdoor advertising and other information sources. However, obtainment of competent inquiry answers by telephone remains a problem. People often choose between organizations depending on quality of the obtained information. Apparently, the issue can be resolved by establishing call centers that are not merely communications centers, but are staffed with competent trained personnel, who support the organization’s interaction with patients (or the legal representatives thereof). The article presents the authors’ experience of establishing a call center dedicated to the organization’s public image development, as well as higher demand of the available services and promotion thereof. The fulfilled modernization resulted in a sharp increase in the amount of calls received (1,500‑1,600 within the working hours; 900 – before modernization) and reduction in the number of complaints of busy line.